Sleep problems and computer use during work and leisure: Cross-sectional study among 7800 adults. (26th November 2015) - Andersen, Lars Louis; Garde, Anne Helene
Abstract : Previous studies linked heavy computer use to disturbed sleep. This study investigates the association between computer use during work and leisure and sleep problems in working adults. From the 2010 round of the Danish Work Environment Cohort Study, currently employed wage earners on daytime schedule ( N  = 7883) replied to the Bergen insomnia scale and questions on weekly duration of computer use. Results showed that sleep problems for three or more days per week (average of six questions) were experienced by 14.9% of the respondents. Logistic regression analyses, controlled for gender, age, physical and psychosocial work factors, lifestyle, chronic disease and mental health showed that computer use during leisure for 30 or more hours per week (reference 0–10 hours per week) was associated with increased odds of sleep problems (OR 1.83 [95% CI 1.06–3.17]). Computer use during work and shorter duration of computer use during leisure were not associated with sleep problems. In conclusion, excessive computer use during leisure – but not work – is associated with sleep problems in adults working on daytime schedule.